Investigation of measurement between gtem cell, anechoic chamber and simulation at 2.4ghz, 5.8ghz and uhf - Khairul Azwan Bin Ahmad (School Of Computer And Communication Engineering, University Malaysia Perlis, 2015)
A fixed environment such as an anechoic chamber is conventionally used to measure the antenna's radiation pattern and reflection coefficient. In this dissertation, instead of anechoic chamber, GTEM cell has been used to measure the radiation pattern of Antenna Under Test (AUT) at three different frequencies of UHF, 2.4GHz and 5.8GHz. The AUT is measured at different polarization namely are E-co, E-cross, H-co and H-cross polarization for the three different frequencies. The results observed that GTEM cell is comparable with anechoic chamber to be use for measurement of antenna in term of radiation pattern. GTEM cell able to give the best result of radiation pattern if low frequency antenna is being measured.